Water surface profiles in side channel spillways : comparisons between computed and experimental values - Cullen, James (Department of Civil Engineering, 2016)
This thesis is an investigation into the water surface profiles found in side channel spillways. The classical method proposed by Hinds is investigated, with specific reference to the water surface slope equation. A literature review is given on the evolution of the theory, from the conceptual ideas of Hinds through to a systematic method of analysis. Experimental methods used over the years are also discussed. A computer program called WSPISCS (Water Surface Profiles In Side Channel Spillways), is developed to calculate the water surface profile. This in turn alleviates the laborious and tedious hand calculations necessary in the past. An iterative, step by step calculation of the water surface profile from .a known control point is conducted. A Runge Kutta fourth order algorithm is employed for the numerical integration. The program is verified with previous hand calculated examples, including the classical example calculated by Hinds. A thorough sensitivity analysis is conducted with regard to the magnitude of the step length, and also to the location of the starting point. Comparisons are made with experimental results obtained over a number of years of undergraduate research. The correlation between the calculated and experimental profiles is generally good. The only exception is a horizontal receiving channel with a hydraulically steep outflow chute, where the experimental profile falls below the calculated one as the inflow rate increases.